Effects of dot-type electroless nickel plating on the mechanical properties of glass/epoxy used for radar-absorbing structures. (1st February 2021) - Jang, Min-Su; Choi, Jae-Hun; Jang, Woo-Hyeok; Nam, Young-Woo; Kim, Chun-Gon
Abstract: Recently, studies have been conducted to implement radar-absorbing structures by electrolessly plating metal on fibers in the form of dots. However, research on the mechanical properties of these dot-type electroless plated composite materials is insufficient. In this study, we aim to investigate the effects of this dot-type plating on the mechanical properties of composite materials. To evaluate these effects, tensile and pull-out tests were performed on single fibers, and tensile, compression, and short-beam shear tests of the laminates were performed. The results indicate that the tensile strength of a single fiber was decreased by the plating process, but the improvement of the interfacial shear strength between the fibers and epoxy owing to the surface modification of the fibers increased the compressive and interlaminar shear strengths. This indicates that the composites with dot-type electroless plating can be applied to actual structures such as stealth aircraft from a structural point of view.